COVID-19 AND THE CHALLENGES OF E-LEARNING IN, SINDH PAKISTAN - Tazeen Shah1, Jamshed Warsi2, Benazir Mahar3, Farheen Shaikh4, Shafaq Ansari5, Sikandar Ali Sial6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2021)
OBJECTIVE: to have a well improved understanding of the attitude of students for the effectiveness of E- learning in higher education institutes in Hyderabad, Sindh, Pakistan. METHADOLOGY: A short descriptive survey was conducted from May to June 2020 in three universities of district Jamshoro. The study population was selected by using simple random sampling technique. Total 450 students were selected for this study. A self-structured questionnaire was structured for this study. An online data collection was done from these university students. RESULTS: 450 total study population, with 150 MBBS, students, and 120, engineering students, MBBS, 180 social science students. Female participants (62.2%), mean ±STD 1.4±0.49 of total study population and (37.3%) mean ±STD 1.1±0.4, are males,usage of mobile phones being340(75.6%) of total study population. with a total of 73(16.2%) of total population utilizing laptops for online classes, usage of desktops for online classes is restricted to 24% of study population,The gadget this is least used by university students is the tablets24(5.3%).The satisfaction with e- learning was observed in 8.9%, quality of learning material was appreciated by 44.4%the class preparation was appreciated by 96.4%, student’s population of82.4 complained for teacher student interaction. lack of mental alertness was reported by 57.1%. CONCLUSION: E-learning, that covers education beyond the classroom, is inadequate in universities of Sindh, in the context of accessibility to the internet, electricity crises, the interaction of students and teachers, as well as the ability to question in these online classrooms.